Usage of Plastic Bags and Health Hazards: A Study to Assess Awareness Level and Perception about Legislation Among a Small Population of Mangalore City - Nitin Joseph; Aswin Kumar; Sumanth Mallikarjuna Majgi; Ganesh S Kumar; Raghavendra Babu Yellapur Prahalad (Journal of Clinical and Diagnostic Research, 2016)
Introduction: Plastic bag users are at risk of number of health hazards. There is paucity of data with regard to awareness of health hazards among general population in India. Aim: This study was done to find out the status of awareness of the health hazards associated with the usage of plastic bags among people and their perception towards the legislation prohibiting the usage of plastic bags. Materials and Methods: This cross-sectional study conducted in Mangalore city in August 2013. Data was collected by interviewing any adult member (aged above 18 years) in each of the selected households using an interview schedule. Results: Mean age of the 250 participants was 32.8±10.8 years. Majority 160(64%) were females educated up to undergraduate level or above 187(74.8%). Among the participants 216(86.4%) were aware of the health hazards associated with the use of plastic bags. Awareness was significantly more amongst females (p=0.027), well-educated participants (p=0.004) and among professionals and semi-professionals (p<0.001). There were 50(20%) participants reusing plastic bags for shopping after initial usage. The cloth bags were used for shopping in place of plastic bags by 13(5.2%) participants. Among the participants 213(85.2%) were aware of the legislation banning the use of plastic bags and out of which 166(77.9%) were in its favour. Semi-professionals and students favoured the ban on plastic bags whereas unskilled and semiskilled workers were against the ban (p=0.01). Conclusion: Most of the participants in the settings had the awareness of hazards of plastic bag usage. However, there is a need for spreading the awareness of using alternative strategies and effective implementation of legislation in order to minimize the usage of plastics in the community.